Current Issues in Health Technology Assessment of Cancer Therapies: A Survey of Stakeholders and Opinion Leaders in Australia. (15th June 2022) - Kim, Hansoo; Liew, Danny; Goodall, Stephen
Abstract: Objective: The aim of this study was to find ways of bridging the gap in opinions concerning health technology assessment (HTA) in reimbursement submission between manufacturers and payers to avoid access delays for patients of vital medicines such as oncology drugs. This was done by investigating differences and similarities of opinion among key stakeholders in Australia. Methods: The survey comprised of nine sections: background demographics, general statements on HTA, clinical claim, extrapolations, quality of life, costs and health resource utilization, agreements, decision making, and capability/capacity. Responses to each question were summarized using descriptive statistics and comparisons were made using chi-square statistics. Results: There were ninety-seven respondents in total, thirty-seven from the public sector (academia/government) and sixty from the private sector (industry/consultancies). Private and public sector respondents had similar views on clinical claims. They were divided when it came to extrapolation of survival data and costs and health resource utilization. However, they generally agreed that rebates are useful, outcomes-based agreements are difficult to implement, managed entry schemes are required when data are limited, and willingness to pay is higher in cancer compared to other therapeutic areas. They also agreed that training mostly takes place through on the job training and that guideline updates were a least favored opportunity for continued training. Conclusions: Private sector respondents favor methods that reduce the incremental cost-effectiveness ratio when compared to the public sector respondents. There still exist a number of challenges for HTA in oncology and many research opportunities as a result of this study.